Faktor Prognostik dan Kesintasan Pasien Leukemia Limfoblastik Akut Anak di RSUP Dr. Sardjito, Yogyakarta, 2010–2015 - LUSIA PUTRI WIJAYANTI; EDDY SUPRIYADI (National Cancer Center - Dharmais Cancer Hospital, 2017)
Acute lymphoblastic leukemia (ALL) is the most common hematologic malignancy in children. Improvements in ALL management in developed countries have shown that the survival rate can be up to 90%. This achievement may be attributed to the stratification of therapy based on prognostic factors. This study aims to evaluate the survival rate of childhood ALL at Sardjito Hospital and prognostic factors for survival. Newly diagnosed patients with ALL aged less than 18 years from January 2010 - December 2015 were enrolled. Patients who have previously received chemotherapy, those with ALL type L3, and those with mixed leukemia were excluded. The survival rate was analyzed by Kaplan-Meier method using log-rank test. Cox regression analysis was used to identify prognostic factors. A total of 309 patients were analyzed. The survival rate of childhood LLA in 2010-2015 in Sardjito Hospital was 56.1 ± 3.9%. Risk grouping based on National Cancer Institute is a prognostic factor that influences the survival of childhood LLA. ABSTRAKLeukemia limfoblastik akut (LLA) merupakan keganasan hematologi yang paling sering ditemui pada anak. Perkembangan LLA anak di negara maju menunjukkan kesintasan pasien mencapai 90%. Keberhasilan terapi pada LLA salah satunya adalah karena adanya stratifikasi terapi berdasarkan faktor prognostik yang ada. Penelitian ini bertujuan untuk mengetahui kesintasan pasien LLA anak di RSUP Dr. Sardjito. Pasien berusia di bawah 18 tahun yang terdiagnosis LLA pada Januari 2010–Desember 2015 diikutsertakan dalam penelitian. Pasien yang pernah mendapatkan kemoterapi, LLA tipe L3, dan mixed leukemia dieksklusi. Kesintasan dianalisis dengan metode Kaplan-Meier menggunakan logrank . Analisis Cox regression digunakan untuk mengidentifikasi faktor prognostik. Sejumlah 309 pasien diikutkan dalam analisis. Kesintasan LLA anak tahun 2010–2015 di RSUP Dr. Sardjito sebesar 56,1±3,9%. Pengelompokan risiko berdasar National Cancer Institute (NCI) merupakan faktor prognostik yang berpengaruh pada kesintasan pasien LLA anak.